Suicide terrorism : understanding the nature of the threat. - Lim, Kheng Siang. (2008)
Contemporary discourse on suicide terrrorism is dominated by two approaches. One focuses on the study of individuals who become suicide bombers and the other examines the terrorist groups that adopt suicide terrorism as their modus opernadi. This dissertation accepts the finding of the first approach which points out that suicide bombers are motivated by a variety of very rational reasons into sacrificing their lives.